Home market competitive pressure and the tendency to internationalise: An inverse U-shape - Pascal Mayer; Thomas Schäper (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2024)
Firm internationalisation has been a central topic of scholarly interest in international business for decades. However, the role of competitive pressure in firms' home markets for firm internationalisation has not been investigated for the full variety of market types, despite the central role of competition in firm strategy. In this study, we examine the relationship between home market competitive pressure, operationalised by the concept of market concentration, and firm internationalisation, and propose an inverted U-shape. We find evidence for our hypothesis based on longitudinal data from more than 27,000 firm-year observations between 2007 and 2019. Our results suggest that internationalisation increases with increasing market concentration up to a certain peak, after which internationalisation declines. Moreover, managerial ability and market fluidity intensity are two important contingencies that intensify this relationship and steepen the inverted U-shape. In revealing this non-linear relationship between home market competitive pressure and firm internationalisation, we contribute to the literature on firm strategy and international business. – – Die Internationalisierung von Unternehmen ist ein zentraler Forschungsgegenstand im Bereich des internationalen Managements. Trotz der zentralen Rolle von Wettbewerb für die Unternehmensstrategie wurde die Rolle des Wettbewerbsdrucks in den Heimatmärkten von Unternehmen noch nicht für die gesamte Bandbreite verschiedener Marktformen untersucht. In dieser Studie untersuchen wir den Zusammenhang zwischen dem Wettbewerbsdruck auf dem Heimatmarkt, operationalisiert durch das Konzept der Marktkonzentration, und nehmen eine Beziehung in Form eines umgekehrten U an. Unsere empirischen Untersuchungen auf Basis eines Paneldatensatzes mit mehr als 27.000 Firmenobservationen über einen Zeitraum von 2007 bis 2019 stützen unsere theoretischen Überlegungen. Die Ergebnisse deuten darauf hin, dass Internationalisierung mit zunehmender Marktkonzentration bis zu einem Maximum zunimmt und anschließend sinkt. Zusätzlich untersuchen wir den Einfluss von Managementkompetenz und Marktfluidität als moderierende Faktoren dieses Zusammenhangs. Indem wir den nicht-linearen Zusammenhang zwischen Marktkonzentration und Internationalisierung aufzeigen, leisten wir einen Beitrag in der akademischen Debatte zur (internationalen) Managementforschung.
Keywords: D41; D42; D43; F20; F23; M16; 650; Competition; Concentration; Internationalisation; Managerial Ability; Market Fluidity